THE JARGON USED BY EMPLOYEES OF FOOD AND BEVERAGE SERVICE (FBS DIVISION) AT HOTELS (English Department of Faculty of Tarbiyah and Teachers Training, 2017)
The purpose of this research was to find out the jargon used of phenomenon in the occupation. It focused in employees of Food and Beverage Service (FBS Division) at Hotels. The subjects are fourteen employees consisting of one Food and Beverage Manager, one Food and Beverage Head of Outlets, two Supervisors and ten Waiters/Waitresses at Aria Barito Hotel Banjarmasin. The object is the jargons used while the employees of Food and Beverage Service Division are on duty. The writer uses participant observation, recording or taking note the conversation and documentary techniques. After collected, the data are analysed with theories and explained descriptive-qualitatively. The result of data analysis reveals that there are 54 jargons in Food and Beverage Service Division at Hotels.